MEMBRANE POTENTIAL MODELING IN EXCITABLE CELLS - Yorqin Sattarov; Sabrina Kamolova (Modern American Journals, 2025)
This article focuses on the computational modeling of membrane potentials in excitable cells, such as neurons and muscle fibers. Membrane potential, the electrical voltage difference across the cell membrane, is crucial for the initiation and propagation of electrical signals in excitable tissues. The study reviews various mathematical models that describe ionic currents and membrane dynamics, including the classic Hodgkin-Huxley model and its modern adaptations. Emphasis is placed on how these models capture the complex interplay of ion channels, pumps, and exchangers that regulate cellular excitability. The article also discusses the application of these models in simulating physiological and pathological conditions, providing valuable insights into cellular behavior. Advances in computational techniques have enhanced the accuracy and efficiency of membrane potential modeling, enabling better understanding of excitability disorders and aiding in the design of targeted interventions.
Keywords: Membrane potential, excitable cells, Hodgkin-Huxley model, ion channels, computational modeling, neuronal excitability, action potential, ionic currents, biophysical simulation, electrophysiology.